Pemberdayaan Berbasis Digital bagi Pelaku UMKM - Baiq Dewi Kamariani; Nur Fitri Eka Asbarini; Maya Ulyani; Abdul Chalel Rahman (BADAN PENERBIT STIEPARI PRESS, 2025)
This community engagement initiative aims to enhance the digital capacity of Micro, Small, and Medium Enterprises (MSMEs) in rural areas through the promotion of digital literacy. The program underscores the critical role of digital transformation in expanding market access and increasing the competitiveness of local MSMEs. A participatory educational approach was employed, involving structured training sessions, ongoing mentorship, and collaborative efforts with key village stakeholders. The results indicate a significant improvement in participants' understanding of digital branding, effective use of social media, and the importance of developing a sustainable village-based economic ecosystem